THE EFFECT OF WORK FATIGUE AND SELF-ESTEEM ON ANXIETY LEVELS AMONG MEDICAL PERSONNEL AT KARTINI HOSPITAL, JAKARTA - Josafat Pondang; Kosasih; Ayu Laili Rahmiyati; Farida Yuliaty; Vip Paramarta (RADJA PUBLIKA, 2025)
Work fatigue refers to feelings of tiredness, reduced attention, and a person's response to psychosocial stress over a period of time. Self-esteem is a person's feelings about themselves. Anxiety is a condition that reflects a state of worry, anxiety, and fear. A preliminary survey at Kartini General Hospital, Jakarta, showed that the majority of medical personnel had mild anxiety, average self-esteem, and mild work fatigue. This study aims to determine the effect of work fatigue and self-esteem on the anxiety of medical personnel at Kartini General Hospital, Jakarta. The research method used was quantitative with a cross-sectional study approach using a questionnaire to medical personnel, then analyzed using multiple linear regression. The number of samples was 82 medical personnel according to the established inclusion and exclusion criteria. The results of the study showed a positive and significant relationship between fatigue and anxiety, and a negative but not statistically significant relationship between self-esteem and anxiety. There was a simultaneous relationship between fatigue and self-esteem on anxiety. Work fatigue has been shown to increase medical personnel's anxiety, and conversely, strong self-esteem is a factor that can suppress anxiety. These findings explain that work fatigue and self-esteem play an important role in anxiety